The Influence of Kindergarten Building’s Plan Patterns and Areal Standards in Children’s Unacceptable Behavior - Ali, Ranj Qadir (Sulaimani Journal for Engineering Sciences, 2017)
The research has been done because of the delay and not keep in touch in responding to the requirements of contemporary child needs, which led to occur unlikable acts and unacceptable behavioral practices in kindergarten spaces by the children, that confirms in transforming kindergarten from a knowledge institution to a place which the child acquires unacceptable behaviors. Thus the research tries to explain the type of relationship between the child’s behavior and areal standards of the built environment in the kindergarten, through two main axes, the first axis studies the child and the way they learn behavior and the measuring methods of such behavior according to psychological theories in order to determine the most important indicators which specifies the two behaviors for the study (aggressive and isolation behaviors), while the second axis deals with the kindergarten buildings in terms of its plan and standards to identify the most influential properties on behavior. Therefore, the ex-axes have been applied in the case study to find out the relationship between them which consisted of three stages; the first stage is the general survey for the whole samples (the existed kindergarten buildings in Erbil city till 2014) which are governmental and private kindergartens, the second stage dealt with the selected samples which consisted of all kinds of governmental buildings and with several private kindergartens, while the third stage represents findings out of the case study and determining the relationship of the influential areal standards on the child’s behavior in order to test the research hypothesis. The research concluded that the diversity in plan patterns led to appear various unacceptable behavioral practices in kindergarten spaces, as it found out that the most recorded cases of unacceptable behavior among children were riots and confusion behaviors, then the second one was violent behavior, the third one was destructive behavior and finally was isolation behavior, where the aggressive behaviors are more practiced by the children in kindergarten buildings as compared to isolation behavior. The research also concluded that the aggressive and isolation behaviors of the selected samples are more occurred in the classes compared to other spaces, while these behaviors are less practiced in the toilets ,finally it raises the recommendation for the research.
Keywords: Areal Standards; Kindergarten; Behavior; Erbil City